Patient Acceptance and Intention to Use e-Consultations During the COVID-19 Pandemic in the Eastern Province of Saudi Arabia - Althumairi, Arwa; Hariri, Beyan; Aljabri, Duaa; Aljaffary, Afnan (Frontiers in Public Health, 2022)
Background Over the last decade, the use of digital technology has increased immeasurably and transformed both our personal and professional lives. The medical profession quickly embraced this development, especially after the spread of the COVID-19 pandemic. Medical consultations were transitioned to online settings as a substitute for face-to-face consultations. This exponential acceleration of the use of remote online consultations (e-consultations) was deemed necessary to respond to the impact of the global pandemic. This paper identifies the factors that influence actual patient use and intention to use e-consultations in Saudi Arabia. Methods A cross-sectional survey was distributed online via social media platforms targeting the population living in Saudi Arabia from August to December 2020. The questionnaire measured patient perceptions of and attitudes towards utilising e-consultations using a validated questionnaire informed by the technology acceptance model (TAM). Analyses were performed in SPSS to identify the external factors that influence patients’ actual use of e-consultations and to assess the TAM factors [usefulness, social influence, ease of use] that influence the intention to use e-consultations across both actual users and never-users. Results A total of 150 participants completed the questionnaire; the average age was 38 years old, 85% of the participants were females, and 67% reported never using e-consultations. Additionally, motivation, trust, attitude and social influence were significantly related to participants’ intention to use e-consultations. Conclusion Participants’ trust in and perception of the usefulness of e-consultations were significant factors in their intention to use e-consultation services. Policymakers’ attention to those factors could play a role in increasing public acceptance and use of e-consultations to improve distance medical care. Keywords: e-consultations, TAM, COVID-19, trust, usefulness.